STATISTICAL ANALYSIS OF IS’HOQXON IBRAT’S VOCABULARY (The Conference Hub, 2025)
This article examines the lexical structure of Ishoqxon Ibrat’s works from a historical and etymological perspective. It analyzes the formation of Turkic, Arabic, Persian, and Russian layers, focusing on their phonetic and semantic evolution. The study explores archaic elements, terminological units, phraseological expressions, and onomastic names found in Ibrat’s texts, revealing their role in the development of the Uzbek language. The research highlights the linguistic significance of Ibrat’s intellectual heritage and its contribution to historical lexicology.